2020
DOI: 10.1002/lno.11647
|View full text |Cite
|
Sign up to set email alerts
|

Can zooplankton on the North American Great Plains “keep up” with climate‐driven salinity change?

Abstract: Derek Gray: Assisted in execution of statistical analysis and interpretation of experiments and editing the manuscript. Kayla Tasky: Assisted with ec50 toxicity experiments and the making of chemical treatments, and the maintenance of zooplankton cultures. I would first like to thank my supervisor, Dr. Derek Gray, for giving me incredible opportunities to work in North Dakota and the Northwest Territories, to travel abroad for conferences, and for providing multiple opportunities for authorship. Your ongoing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“… 61 ). Thus, we would not expect evolutionary processes to stabilize the zooplankton–algae energy pathway in freshwater food webs ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“… 61 ). Thus, we would not expect evolutionary processes to stabilize the zooplankton–algae energy pathway in freshwater food webs ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using egg bank-derived clones have revealed idiosyncratic patterns when considered in conjunction with other paleo-indicators. For example, Elmarsafy et al (2020) found that ephippia of the cladoceran, Ceriodaphnia dubia, remained in the egg bank of a naturally saline lake, despite predictions of salinity (from diatom-based transfer functions) exceeding estimated EC 50 for salt during these time periods. Thus, considering additional evidence from other sources (e.g., genetic surveys) from sediment egg banks will be an important next step for increasing our understanding and interpretation of the sediment record in lakes (Frisch et al 2017).…”
Section: Caveats and Conclusionmentioning
confidence: 99%
“…For example, high DOC levels could fuel microbial community diversity in a stressed environment . As brackish lakes are undergoing salinization to brine lakes under climate warming, ,, more carbon tends to accumulate and transform into halocarbon in brine lakes.…”
Section: Discussionmentioning
confidence: 99%